2018
DOI: 10.1017/s2045796018000501
|View full text |Cite
|
Sign up to set email alerts
|

Psychoses sans Frontieres: towards an interdisciplinary understanding of psychosis risk amongst migrants and their descendants

Abstract: Understanding the excess risk of psychotic disorders in migrant and ethnic minority groups has long been an important research focus in psychiatric epidemiology and public mental health. Heterogeneity between migrant groups based on the region of origin, minority status and other socioeconomic factors may provide clues as to the underlying aetiological mechanisms explaining this risk, as well as informing our general understanding of psychotic disorders. Nonetheless, disentangling the mechanisms underlying thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…Persisting experience of social exclusion may result in an alteration of biological function, and is thus introduced as a contributing factor [ 46 ]. A recent scoping review mentioned vitamin D deficiency and complications during pregnancy as other possible biological explanations [ 47 ]. Overall, however, it is suggested that post-migration factors are more relevant than pre-migration factors in explaining the increased risk, as it is shown to persist into the second generation.…”
Section: Discussionmentioning
confidence: 99%
“…Persisting experience of social exclusion may result in an alteration of biological function, and is thus introduced as a contributing factor [ 46 ]. A recent scoping review mentioned vitamin D deficiency and complications during pregnancy as other possible biological explanations [ 47 ]. Overall, however, it is suggested that post-migration factors are more relevant than pre-migration factors in explaining the increased risk, as it is shown to persist into the second generation.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reviews, including our own, have considered the evidence for a range of putative causal factors that may contribute to ethnic variations.…”
Section: Candidate Causesmentioning
confidence: 99%
“…Studies have indeed indicated that immigrants, especially refugees, have a greater risk of developing some mental illnesses than native populations [1,[3][4][5][6]. In many countries, psychotic disorders, mood disorders, and post-traumatic stress disorders have been more common among immigrants than native populations [3][4][5]7].…”
Section: Introductionmentioning
confidence: 99%